You are in charge: Experimentally testing the motivating power of holding a judicial office - Christoph Engel; Lilia Zhurakhovska (Max Planck Institute for Research on Collective Goods, 2016)
Apparently judges' decisions are not motivated by maximizing their own profit. The literature uses two strategies to explain this observation: judges care about the long-term monetary consequences for themselves, or individuals who are more strongly motivated by the common good self-select into the profession. We suggest that there is an additional explanation, the "office motive". In a lab experiment, we rule out both traditional explanations by design. Nonetheless authorities do a reliable job at overcoming a social dilemma. Calling the authorities "public official" or "judge" increases their sensitivity towards the degree by which individuals are selfish, and it reduces the effect of their social value orientation (making them more neutral). This suggests that the socially desirable effect is not driven by anger or sympathy with the victims, but follows from the desire to fulfill the expectations that come with the assigned task. We test three extensions: When given an opportunity to announce an explicit policy, judges become less sensitive to the objective degree of reproach, and more sensitive to their social value orientation. If judges are elected or experienced, they react more intensely to norm violations. Experienced judges are more affected by their social value orientation.
Keywords: C91; D03; D63; D73; H11; H41; H83; K41; 330; judicial behavior; office motive; public-goods experiment; judicial frame; election; experience